The field measurement of suspended sediment in the surf zone - Heidstra, N N (Department of Civil Engineering, 2016)
Suspended sediment concentrations were measured in the nearshore environment at the site of the proposed breakwater of the Koeberg Nuclear Power Station. Reference concentrations are evaluated from the field data. Two sampling systems to obtain these concentrations were designed and constructed. The Mark I sampler was used to collect the field data, whilst the Mark II sampler was extensively tested in the laboratory and the proposed operational system was tested in the field. Difficulties were experienced in the operation of the Mark II sampling system, and are described. Recommendations for the improvement of the sampling systems are given, based on the experience gained using the sampling systems.